2022
DOI: 10.1177/17577438221109907
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ motivation to choose teaching and remain in the profession: A comparative mixed methods study in Jamaica, Poland and Turkey

Abstract: The comparative, mixed methods international and cross-cultural study aimed to determine the factors that motivated teachers in Jamaica, Poland and Turkey to choose teaching as a career and ascertain what motivated the teachers at different stages to remain in teaching. Data were collected through the use of the questionnaire, which experts validated and had an overall reliability coefficient of 0.77 and focus group interviews. A total of 186 teachers participated in the quantitative phase of the study, whilst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 70 publications
0
0
0
Order By: Relevance
“…Theoretical frameworks provide insights into this relationship (Li et al, 2023). Crosstabulation data among private teachers reveals a balanced distribution between those intending to stay and those not, indicating the need for further analysis of retention strategies (Onyefulu et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…Theoretical frameworks provide insights into this relationship (Li et al, 2023). Crosstabulation data among private teachers reveals a balanced distribution between those intending to stay and those not, indicating the need for further analysis of retention strategies (Onyefulu et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…According to Greenglass and Burke (2003), teaching is generally considered one of the most rewarding professions in terms of job satisfaction. Onyefulu et al (2022) also found some factors that motivates teachers to stay in the profession such as, the sense of vocation, job satisfaction, desire to teach, desire to make a positive impact on students' lives, and all the rewards related to teaching profession.…”
Section: Literature Reviewmentioning
confidence: 97%
“…It can be indicated that staying as friendly as possible to address teacher problems and questions was emphasized as an important point. Once it is acknowledged that administrators are available to provide support with their concerns, teachers will feel more relaxed and encouraged (Onyefulu et al, 2023). Pink (2011) emphasized that administrator's support, autonomy, justice, self-development and appreciation increases the internal motivation of the teacher by developing a sense of belonging to the institution.…”
Section: Schoolsmentioning
confidence: 99%
“…Effective comminucation strategies will lead meaningful task assignments which will also lead instrintic motivation (Gür et al, 2021). Onyefulu et al,(2023) suggested motivational enhancement training for administrators in order to use motivational strategies effectively for the motivation and vocational-outcome expectations of the teachers.…”
Section: Schoolsmentioning
confidence: 99%